Pollution Study on the River Lėvuo - Karalius, Ovidijus; Tričys, Vaclovas (Jaunųjų mokslininkų darbai, 2018)
The article aims to investigate the Lėvens river water quality. Authors analyse the surface water protection issues in scientific literature. Moreover, provide knowledge about the condition of the Lėvens river. In addition, the article aims to calculate the quantities of pollutants from the Svalia river to the Lėvuo river and select the Lėvens on the river which was 10 points. Water samples are taken and tested: water temperature, pH, amount of suspended matter, dissolved oxygen content, biochemical oxygen consumption in 7 days, ammonium nitrogen, total nitrogen, nitrate, and total phosphorus and phosphate concentrations. The study was conducted on one occasion: the first time the samples were taken in April.In analysed water examples pH varied from 7,53 to 8,01. The concentration of the suspended matter in suspension water samples ranged from 8,9 mg/l up to 17,6 mg/l and has not been exceeded by one. The total nitrogen concentration in the samples ranged from 3,89 mg/l to 4.38 mg/l. The concentration of total nitrogen has exceeded all points in the river. The capped maximum nitrate concentration reached 2.47 mgN/l. Nitrate concentrations in other investigated rivers range from 1.37 mgN/l to 2.23 mgN/l, but the limit values do not exceed. The highest concentrations of total phosphorus in the Levuo river are found in the mouths of the Svalia river. The permissible concentration limit value exceeded 0.059 mgP/l.According to the results of the samples obtained by comparison with Pasvalio city administrative division monitoring, the Levens river condition evaluated atmedium.
Keywords: river; pollutants; tributary; concentration; monitoring; nitrogen; phosphorus